PHYSIOLOGICAL LEVELS OF TRIIODOTHYRONINE, THYROXINE AND CORTISOL IN GROWING SWAMP BUFFALO CALVES (Indian Journal of Animal Production and Management, 2014)
Ten numbers of growing swamp buffalo calves were selected irrespective of sex and divided into two groups comprising 5 animals in each. About 5 ml of blood was collected from each of the experimental animal both in the morning and in the afternoon at 15 days intervals during the period between March and August. Hormone T3, T4 and cortisol were estimated from serum by Radio-Immuno Assay . The mean values of Triiodothyronine, Thyroxine and Cortisol ranged from 1.00 ± 0.28 to 1.08 ± 0.30, 44.20 ± 1.20 to 46.30 ± 1.20 and 60.26 ± 1.36 to 62.75 ± 1.07 nmol/l respectively. Present study revealed that serum T3 were below normal in both the groups. Serum T4 levels were found within the normal value. However, serum cortisol levels were found to be higher than the normal value in both the groups during pre-monsoon and monsoon periods.
Keywords: Swamp buffalo calves; serum; Triiodothyronine (T3); Thyroxine (T4); Cortisol; premonsoon and monsoon